Extraction and Characterization of Bacteriocin Produced by Leuconostoc mesenteroides SM 22 - Darnawan Ari Nugroho; Endang S Rahayu (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2003)
Bacteriocin produced by lactic acid bacteria has potential as food biopreservative due to their capability to control spoilage and pathogenic food borne bacteria. Previous studies showed that extraction of bacteriocin produced by Leuconostoc mesenteroides SM 22 using adsorption-desorption method was not optimal. The objectives of this research were (1) to increase the effectiveness of bacteriocin extraction using adsorption-desorption method by the addition of heated biomass of Leuconostoc SM 22 in various concentration during adsorbtion (2) to characterize the bacteriocin of Leuconostoc mesenteroides SM 22 on it's stability during heat treatment, during cool storage and it's spectrum activity againts pathogenic bacteria. Result of this research showed that bacteriocin activity obtained from extraction with no addition of heated biomass was 1000 AU/ml, while by addition of heated biomass of 2 to 3 times of original concentration (OD) were 2000 AU/ml. Therefore it was suggested that addition of heated biomass of Leuconostoc mesenteroides SM 22 during adsorption-desorption with 2 times of original concentration (OD) was able to increase the bacteriocin obtained. Bacteriocin with original activity of 2000 AU/ml, was stable (no reduction activity) after heated at 100oC for 30 minutes, but slightly decrease after heated at 121oC for 5 minutes and 121oC for 15 minutes, that were 1600 AU/ml and 800 AU/ml respectively. Bacteriocin of Leuconostoc mesenteroides SM 22 was stable during 8 weeks storage at refrigerator (4oC), freezer -20oC and -40oC. This bacteriocin has a wide spectrum of activity showed by it's ability to inhibit the growth of Listeria monocytogenes, Staphylococcus aureus, Salmonella thypimurium, Vibrio parahaemolyticus, Shigella and psychrophilic bacteria isolated from milk and isolated from meat. Key words : Bacteriosin, leuconostoc mesenteroides.